2007
DOI: 10.1007/s12079-008-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide donor and gamma irradiation on modifications of ERK and JNK in murine peritoneal macrophages

Abstract: Mitogen activated protein kinases (MAPKs) play an important role in activation, differentiation and proliferation of macrophages. Macrophages, upon activation, produce large amounts of nitric oxide that inhibit the growth of variety of microorganisms and tumor cells. This nitric oxide which is known to interfere with tyrosine phosphorylation may result in changes in the pattern of activation of MAPKs. In a previous study we have found that tyrosine phosphorylation of MAPKs was completely abolished in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…59,75 Nitric oxide is known to interfere with tyrosine phosphorylation and can either diminish the efficacy of a protein as a substrate for tyrosine kinases or lead to their activation by increased phosphorylation directly [76][77][78] or by inactivation of phosphatases. 79 The production of large amounts of NO during inflammatory challenge leads to the formation of reactive nitrogen species/reactive oxygen species capable of oxidizing many biological molecules including protein tyrosine nitration. 80 A series of studies demonstrated protein nitration in the human atherosclerotic tissue.…”
Section: Role Of Enos In Cardiovascular Systemmentioning
confidence: 99%
“…59,75 Nitric oxide is known to interfere with tyrosine phosphorylation and can either diminish the efficacy of a protein as a substrate for tyrosine kinases or lead to their activation by increased phosphorylation directly [76][77][78] or by inactivation of phosphatases. 79 The production of large amounts of NO during inflammatory challenge leads to the formation of reactive nitrogen species/reactive oxygen species capable of oxidizing many biological molecules including protein tyrosine nitration. 80 A series of studies demonstrated protein nitration in the human atherosclerotic tissue.…”
Section: Role Of Enos In Cardiovascular Systemmentioning
confidence: 99%
“…However, the third isotype, calcium-independent NOS, i.e., iNOS, is typically expressed in response to proinflammatory stimuli (51). NO can react with reactive oxygen species (ROS) to form peroxynitrite that may lead to nitrosylation or nitration on tyrosine residues of proteins (52,53) and thus alter the activities of these proteins. The small quantity of NO generated through eNOS has a protective effect in atherosclerotic lesions (54).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, EL4 cells show many fold increase in basal levels of SOD activity as compared to RAW264.7 cells and splenocytes. NO is known to react with reactive oxygen species to form peroxynitrite, which may lead to nitrosylation or nitration of proteins on tyrosine residues (Beckman and Crow 1993;Narang et al 2007) thus altering their activities. Moreover, catalase, which contains a heme group, also could be highly susceptible to nitric oxide mediated modification (Pietarinen et al 1995;Wassmann et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide production was estimated by measuring NO 2 − concentration with Griess Reagent (1% sulfanilamide, 0.1% napthylene diamine dihydrochoride, and 2.5% H 3 PO 4 ) as described by Ding et al Briefly, aliquots (100 μl) of culture supernatants (5′, 15′, and 30′ and 1, 4, 6, 8, 18, and 24 h) were incubated with an equal volume of Griess Reagent at room temperature for 10 min, and the absorbance at 550 nm (Narang et al 2007). …”
Section: Cell Viability-dye Exclusion Testmentioning
confidence: 99%